Beers versus STOPP criteria in polyharmacy community-dwelling older patients - 10.7399/fh.2016.40.3.9706; Maria Esther Salgueiro-Vázquez; Francisco José Jimeno-Demuth; Gloria Manso (Elsevier, 2016)
Objective: To assess potentially inappropriate prescribing (PIP) using Beers (2012 version) and STOPP (2008 version) criteria in polypharmacy, community-dwelling, older patients. Methods: From the information collected in the invoicing data of the prescriptions and the electronic medical records, a sample was selected of 223 ≥ 65-year-old patients who were taking simultaneously 10 or more drugs per day. Beers and STOPP criteria were separately applied, and the results obtained with the two methods were compared. Results: A total of 141 (63.2%) patients presented at least one Beers criterion. The two most frequently observed Beers criteria independent of diagnosis were the use of benzodiazepines and the use of non-COX-2-selective non-steroidal anti-inflammatory drugs. With regard to Beers criteria considering diagnosis, the most frequent were the use of anticholinergic drugs in patients with lower urinary tract symptoms or benign prostatic hyperplasia, and the use of benzodiazepines, antipsychotics, zolpidem or H2-antihistamines, in patients with dementia or cognitive impairment. A total of 165 (73.9%) patients had at least one PIP according to the STOPP criteria. Duplicate drug classes and long-term use of long-acting benzodiazepines were the two most frequent STOPP criteria. Discussion: Our study identified a high frequency of PIP in polymedicated community-dwelling older patients. Simultaneous application of Beers and STOPP criteria represents a useful tool to improve prescribing in this population group.